KONTRIBUSI PEMBELAJARAN IPS DALAM MEMBENTUK KARAKTER ANAK SEKOLAH DASAR - I Made Oka Adi Winata; I Wayan Lasmawan; I Wayan Kertih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In the era of Society 5.0, technological developments bring great changes that affect social life and present moral challenges, especially among the younger generation. Indonesia is facing a moral crisis involving various social problems that threaten the future of the nation. Character education is one of the important solutions to overcome this cases, with an emphasis on early education at the elementary school level. The method applied literature study by analyzing various relevant literature sources on character education and social studies learning. The results show that social studies learning can serve as an important tool in shaping the character and social skills of students. It expected to grow a young generation that is not only academically intelligent, but also has high integrity and morality. In conclusion, social studies learning has a strategic role in supporting character education, which is important to create active individuals in building a dignified nation.